Value co-creation between coworking spaces and startups in different stages of development - Barajas, Giuliana; Fleury, André Leme (Revista Gestão da Produção Operações e Sistemas, 2024)
Purpose – This study identified, characterized, and evaluated the relevance of the services provided by Coworking spaces considering the different stages in the evolution of a startup. Design/methodology/approach – A narrative literature review was conducted and the second phase of the research included the development of netnographic initiatives and the conduction of multiple case studies. Findings – As a result, six categories of services were identified, comprehending 36 services, whose relevance varies considering the maturity level of the startup. Originality/value – This research contributes to the literature by providing a systemic view of the state of practice of these services in the context of Coworking spaces. Keywords - Coworking Space. Startup. Sharing economy. Co-creation. Digital transformation.